Inovasi Mikrostruktur Produksi Diecast Costum SMK Muhammadiyah 1 Kabupaten Magelang sebagai Penguatan Sumber Daya Manusia - Salimah Tamam (Jurnal Al-Tatwir, 2022)
To achieve this, SMKs need to make efforts so that their graduates are able to compete in getting jobs or creating jobs, and are able to compete in employment. With the ability of SMK graduates to create jobs and the ability to compete for jobs, it is expected to reduce the unemployment rate in Indonesia which is still high. This research is a qualitative research where a good research always pays attention to the suitability between the techniques used with the general flow of thought and theoretical ideas. And strengthening human resources by empowering the diecast custom community invites the surrounding community to embrace them by developing their talents and interests and getting side jobs from the daily profession of the community itself. The annual nominal value can be 12,000,000 because of the pre-order (PO) marketing system. And the marketing of die-cast production can be seen from the data that in the MINI SMK Custom Diecast Plan, revenue is taken from the MINI SMK program with a total fixed and variable financing of up to Rp. 30,000,000.00 - while the income earned from the Custom Diecast business is greater than the risks faced by the Production Unit (UP) because the sales system uses a Pre Order (PO) system.